Сучасні перспективи розвитку селянських домогосподарств - Кальченко, Сергій Володимирович; Кальченко, Сергей Владимирович; Kalchenko, Serhii (My University, 2013)
EN: The article analyzes the ways of reorganizing small agrarian enterprises taking the case study of farm households. Special attention is paid to maintaining the optimal usage of land and labour resources. UA: У статті проаналізовано шляхи розбудови дрібного аграрного підприємництва на прикладі селянських домогосподарств. Особливу увагу приділено забезпеченню оптимального використання земельних та трудових ресурсів.
Сurrent development prospects of farm households
Keywords: agrarian entrepreneurship; farm household